Observation and trapping of insects visiting male and female inflorescences of oil palm - Mohd Faizal Sedie; Mohamad Rosman Sulaiman; Muhammad Azmi Mohammed; Siti Nurulhidayah Ahmad Mohamed; Mazmira Mohd Masri; Saharul Abillah Mohamad; King Jie Hung (Penerbit Universiti Kebangsaan Malaysia, 2024)
The African oil palm, Elaeis guineensis, relies heavily on entomophily. The absence of insect pollinators will cause inadequate fruit setting and in extreme situations, triggering bunch failure, especially in young palms. Fruit bunches of high quality are produced with adequate pollination, ensuring a high rate of oil extraction. The presence of the oil palm pollinating weevil, Elaeidobius kamerunicus in both sexes of the oil palm inflorescence is well-documented. However, reports on the presence of other insects, which may provide complementary pollination services, are still lacking. In addition, the presence of native oil palm pollinators in Sarawak was not recorded before the introduction of the weevil in the early 1980s. As such, this study investigates the presence of insect visitors and activity on sixteen male and female oil palm inflorescences at MPOB Sessang Research Station, Sarawak, Malaysia. The male inflorescences attracted more insect visitors than the female, as 87.6% of the insects were captured on the male inflorescences. From a total of 16 insect morphospecies identified, the two most abundant species caught were E. kamerunicus and Pyroderces sp. In addition, a host of other insect species were also observed, frequenting both sexes of the inflorescences. These insects may serve their respective ecological functions on oil palm inflorescences. Here, the presence of one of the native oil palm pollinators, Pyroderces sp. in Sarawak was confirmed, which has not been previously reported.